2018
DOI: 10.1002/jae.2670
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of grade retention in high school

Abstract: Summary A dynamic discrete‐choice model is set up to estimate the effects of grade retention in high school, both in the short run (end‐of‐year evaluation) and in the long run (drop‐out and delay). In contrast to other evaluation approaches, this model captures essential treatment heterogeneity and controls for grade‐varying unobservable determinants. In addition, forced track downgrading is considered as an alternative remedial measure. Our results indicate that grade retention has a neutral effect on academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…At later grades, retention is harmful. It reduces student achievement and high school completion (Cockx et al, 2018;Jacob & Lefgren, 2009) and increases the risk of being convicted of a crime by age 25 (Eren et al, 2018).…”
Section: Black-white Grade Retention Gapsmentioning
confidence: 99%
“…At later grades, retention is harmful. It reduces student achievement and high school completion (Cockx et al, 2018;Jacob & Lefgren, 2009) and increases the risk of being convicted of a crime by age 25 (Eren et al, 2018).…”
Section: Black-white Grade Retention Gapsmentioning
confidence: 99%
“…As for studies that assess the effect of grade retention in secondary level, Brodaty et al (2014) showed that the elasticity with respect to grade repetition risk (or risk of delay) is negative and very important regarding enrolment in college in France. Cockx et al (2019) found that pupils repeating (for the first time) grade 8 have a 14 percentage point lower chance of graduating from high school. Moreover, Mahjoub (2017) concluded that grade repetition improves the probability of graduating from junior high school by 2.5 probability points using IV and matching estimators.…”
Section: Impact Of Grade Retention On Other Educational and Labour Mamentioning
confidence: 95%
“…The data for the empirical research came from the SONAR survey (Baert & Cockx, 2013; Baert et al, 2013; Cockx et al, 2019; SONAR, 2000), created to study how Flemish youth make the transition from school to work. Flanders is the Northern, Dutch‐speaking part of Belgium.…”
Section: Methodsmentioning
confidence: 99%
“…This school delay is represented in approximately 9% of the individuals in our data. For more details on the educational system in Flanders, see Baert and Cockx (2013), Baert et al (2013), Cockx et al (2019), and De Ro (2008).…”
Section: Methodsmentioning
confidence: 99%